Philosophy and the Question of Social Relevance - Adefarasin, V. O. (NIU Journal of Humanities, 2022)
The paper argues the thesis that Philosophy is relevant to our society. This is against the general erroneous and misconception that Philosophy, being an abstract discipline, has no practical relevance on our lives. The Anglo-Saxon analytic tradition lends support to this misconception by reducing Philosophy to analysis alone. As it has been conceived and developed in the West, and elsewhere, and in our contemporary society through the Ages, Philosophy has played and will continue to play vital roles in the development of our society. In order to achieve its intended objective therefore, the paper discusses meaning and definition of Philosophy, branches of Philosophy, â€œthe ten commandmentsâ€ of Philosophy. The paper concludes that Philosophy contributes meaningfully to the growth of any society. Keywords: Philosophy, question and social relevance.